2020
DOI: 10.2147/copd.s238408
|View full text |Cite
|
Sign up to set email alerts
|

<p>Patient Characteristics and Healthcare Resource Utilization Among Patients with COPD New to LAMA/LABA Fixed-Dose Combination Treatment in US-Based Real-World Practice</p>

Abstract: Introduction: This retrospective, observational cohort study utilized an integrated dataset from an electronic health records system and a claims database to describe demographic and clinical characteristics, healthcare resource utilization (HCRU), and treatment patterns in COPD patients initiating long-acting muscarinic antagonist (LAMA)/long-acting β 2 -agonist (LABA) fixed-dose combination (FDC) treatment in the USA. Methods: Patients were aged ≥40 years and had a COPD diagnosis (Practice Fusion system) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…In general, the clinical characteristics of patients with COPD who initiated BGF in this AURA study were similar to patients who initiated FUV or MITT, as reported in previous studies, 12 , 18 with the majority being 65 years or older, female, and Medicare beneficiaries. Consistent with findings of these two previous studies describing patients initiating FUV and MITT, 11 , 12 a high proportion of patients initiating BGF in our study had cardiopulmonary-related comorbidities, indicating that the presence of such comorbidities may also play a role in prescribing decisions of TT in real-world practice.…”
Section: Discussionsupporting
confidence: 82%
“…In general, the clinical characteristics of patients with COPD who initiated BGF in this AURA study were similar to patients who initiated FUV or MITT, as reported in previous studies, 12 , 18 with the majority being 65 years or older, female, and Medicare beneficiaries. Consistent with findings of these two previous studies describing patients initiating FUV and MITT, 11 , 12 a high proportion of patients initiating BGF in our study had cardiopulmonary-related comorbidities, indicating that the presence of such comorbidities may also play a role in prescribing decisions of TT in real-world practice.…”
Section: Discussionsupporting
confidence: 82%
“…Mean 1-year per-patient all-cause costs from IDV® in 10,140 patients with epilepsy without tuberculosis sclerosis complex was reported to be $56,397 ( 24 ), while total cost over 5 years was reported at $47,464 (average of $9492.80 per year) for 15,599 patients with rheumatoid arthritis who used oral methotrexate only ( 25 ). For 7043 patients with chronic obstructive pulmonary disease, 1-year all-cause costs from IDV® were reported at $19,690.40 ( 26 ). Though direct comparisons cannot be made due to non-trivial differences in cost estimation algorithms (i.e., charged vs. paid amounts), it is apparent that costs for gMG lie in the higher range within these relatively age-matched chronic conditions, with exacerbations and crisis events causing costs to rise even further.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to initiating nebulized GLY, one in five patients had chronic respiratory failure, one in four patients had influenza or respiratory infection, and nearly one in three patients had a CCI score of at least 3. Compared to other COPD studies using U.S. claims data, higher proportions of patients in this study used ICS (31% versus 3% to 21.6% [24][25][26][27][28] ) OCS (69% versus 14% to 49% 25,27,29,30 ) SABA (65% versus 20% to 54% [25][26][27][29][30][31] ) or SAMA (10% versus 1% to 8% [25][26][27]29 ) during the pre-index period. As corticosteroids (ICS or OCS), shortacting agents (SAMA or SABA), and antibiotics are treatment options for the treatment of acute exacerbations 6 , the high use of these therapies during the pre-index period suggests a population with a history of exacerbations, which is a risk factor for future exacerbations 7 .…”
Section: Discussionmentioning
confidence: 63%